(untitled) (Advancements in Homeopathic Research, 2022)
A 28 year old female, a well diagnosed case of SLE having disease activity index SLEDAI – 7. The patient suffered from shifting polyarthralgia with swelling in the wrist joint, recurrent sore throat, generalized weakness and alopecia, failed to improve clinically under allopathic treatment. Laboratory data revealed, anemia (Hb% = 9.9), leucopenia (WBC = 2530 /cu mm), thrombocytopenia (1.29 lac / cumm) and the most significant, Anti Nuclear Antibody POSITIVE (3+ in 1:100 dilution, homogenous pattern), Anti Ds DNA (ELISA) POSITIVE (112 IU/ml). Patient was treated for 2 years with homoeopathic medicines selected based on the individualistic peculiar symptoms and specific pathological manifestation to reduce the intensity of the symptoms. This approach made the patient to recover clinically without any relapse and with improved quality of life. Ultimately, the favorable serological data of Anti Ds DNA- NEGATIVE (18 IU/ml), Anti Nuclear Antibody POSITIVE (2+ in 1:100 dilution, homogenous pattern) confirmed the efficacy of Homoeopathy.